"Material Autonomy and spiritual Equality: A Comparative Study of Feminist Thought in A Room of One's Own and Woman in the Nineteenth Century" (Al-Farooq Journal of Sciences, 2026)
This paper presents a comparative analysis of feminist thought in A Room of One’s Own (1929) by Virginia Woolf and Woman in the Nineteenth Century (1845) by Margaret Fuller. Both authors critique patriarchal structures and advocate women’s emancipation, yet they differ in their approaches. Woolf emphasizes economic independence and personal space as essential conditions for female creativity, while Fuller highlights spiritual growth, intellectual development, and equality within social and religious frameworks. The study argues that, despite these differences, both texts contribute significantly to early feminist discourse and remain relevant to contemporary discussions on gender equality.
Keywords: Financial independence - Spiritual equality - Feminist thought - Women - 19th century